The impact of intermediate-term alcohol abstinence on memory retrieval and suppression - Nemeth, Viola L.; Kurgyis, Eszter; Csifcsak, Gabor; Maraz, Anikó; Almasi, Denes A.; Drotos, Gergely; Szikszay, Petronella; Ando, Balint; Janka, Zoltán; Must, Anita (Frontiers in Psychology, 2014)
Background: The nature of episodic memory deficit in intermediate-term abstinence from alcohol in alcohol dependence (AD) is not yet clarified. Deficits in inhibitory control are commonly reported in substance use disorders. However, much less is known about cognitive control suppressing interference from memory. The Think/No-think (TNT) paradigm is a well established method to investigate inhibition of associative memory retrieval. Methods: Thirty-six unmedicated alcohol dependent (AD) patients and 36 healthy controls (HC) performed the TNT task. Thirty image-word pairs were trained up to a predefined accuracy level. Cued recall was examined in three conditions: Think (T) for items instructed to-be-remembered, No-think (NT) assessing the ability to suppress retrieval and Baseline (B) for general relational memory. Premorbid IQ, clinical variables and impulsivity measures were quantified. Results: AD patients had a significantly increased demand for training. Baseline memory abilities and effect of practice on retrieval were not markedly different between the groups. We found a significant main effect of group (HC vs AD) x condition (B, T and NT) and a significant difference in mean NT-B scores for the two groups. Discussion: AD and HC groups did not differ essentially in their baseline memory abilities. Also, the instruction to focus on retrieval improved episodic memory performance in both groups. Crucially, control participants were able to suppress relational words in the NT condition supporting the critical effect of cognitive control processes over inhibition of retrieval. In contrast to this, the ability of AD patients to suppress retrieval was found to be impaired.